An image based visual servoing approach for multi-target tracking using an quad-tilt rotor UAV - Zarudzki, Mateusz; Shin, Hyo-Sang; Lee, Chang-Hun (Institute of Electrical and Electronics Engineers (IEEE), 2017)
This paper proposes a guidance algorithm of a UAV for multiple targets tracking, considering physical constraints of the platform and its sensor. The on-board sensor used for target tracking is a camera. To relax the need of a gimbal system and provide flexibility in utilisation of the vision sensor, a new rotorcraft type of UAV is developed. The main focus in designing tracking guidance is to develop an image based visual servoing approach, appropriate to the newly developed platform. A complementary to the guidance system a control system for the unconventional UAV is also presented. Both control and guidance algorithms are based on the PID control techniques and this paper shows that the tracking guidance can be significantly simplified with the new type of UAV developed. The performance of the proposed tracking guidance along with the controller designed is validated by numerical simulations and flight tests.
Keywords: Target tracking; Cameras; Algorithm design and analysis; Mathematical model; Rotors; Visual servoing; Unmanned aerial vehicles